2019
DOI: 10.1029/2018jb016617
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Alteration and Fracture Influence on the Elastic Properties of Volcaniclastic Rocks

Abstract: In geothermal environments, the physical properties of rocks, such as porosity and alteration, are highly variable and control the reservoir's elastic and hydraulic properties. Elastic wave velocity in volcaniclastic rocks and their relation to fractures, pore shapes, and mineral alteration is mostly unknown. We measure ultrasonic P and S wave speeds on volcanic rocks from the Ngatamariki Geothermal Reservoir, New Zealand. Data clustering of wave speed versus porosity and density allow us to classify lithotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 62 publications
2
11
1
Order By: Relevance
“…Our data show that Young's modulus decreases as a function of increasing porosity (Figure 7), in agreement with previous studies (e.g., Heap et al, 2020b). Chemical alteration is also known to influence the Young's modulus of rocks and can result in increases to Young's modulus when the alteration is pore-filling (e.g., Frolova et al, 2014;Mordensky et al, 2018;Durán et al, 2019) and decreases to Young's modulus in the case of dissolution (e.g., Frolova et al, 2014). The low Young's modulus of samples from Aumühle (Figure 7) can therefore be explained by a combination of their higher porosity and greater degree of alteration.…”
Section: 2supporting
confidence: 92%
“…Our data show that Young's modulus decreases as a function of increasing porosity (Figure 7), in agreement with previous studies (e.g., Heap et al, 2020b). Chemical alteration is also known to influence the Young's modulus of rocks and can result in increases to Young's modulus when the alteration is pore-filling (e.g., Frolova et al, 2014;Mordensky et al, 2018;Durán et al, 2019) and decreases to Young's modulus in the case of dissolution (e.g., Frolova et al, 2014). The low Young's modulus of samples from Aumühle (Figure 7) can therefore be explained by a combination of their higher porosity and greater degree of alteration.…”
Section: 2supporting
confidence: 92%
“…The secondary mineralogy observed here is in contrast to the mineralogy of chlorite, epidote, smectite, observed in the geothermal reservoirs of Taupo Volcanic Zone (Durán, Adam, Wallis, & Barnhoorn, 2019; Wyering et al., 2014). This is likely due to the acidic nature of fluids at Whakaari compared to near‐neutral thermal waters observed in other long‐lived geothermal systems (Giggenbach et al., 2003).…”
Section: Resultscontrasting
confidence: 84%
“…Durán et al. (2019) and others have discussed how the conventional crack density parameter, Γ , should be converted to crack porosity in order to be physically meaningful, but here we are questioning the validity of the parameter itself, which is based on elliptical (or usually, circular) cracks. For instance, as Gurevich et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, extracting true crack densities is somewhat elusive. Durán et al (2019) and others have discussed how the conventional crack density parameter, Γ, should be converted to crack porosity in order to be physically meaningful, but here we are questioning the validity of the parameter itself, which is based on elliptical (or usually, circular) cracks. For instance, as Gurevich et al (2009) have shown, there is often a large discrepancy between crack density parameters (Γ K and Γ G , respectively) calculated from the effective bulk and shear moduli using the equations of O' Connell and Budiansky (1974).…”
Section: Table 1 Compliance Ratios and Crack Densities From Stress-dependent Velocitiesmentioning
confidence: 99%